THE INFLUENCE OF RELIGIOUS BEHAVIOR ON CONSUMERS’ INTENTION TO PURCHASE HALAL-LABELED PRODUCTS - Muniaty Aisyah (Business and Entrepreneurial Review, 2014)
The purposes of this research are to analyze the influence of consumers’ religious behavior on their intention to purchase halal-labeled products, and also to analyze whether consumers with Islamic educational background are different from consumers with general educational background in terms of their religious behavior and their intention to purchase halal-labeledproducts. This research uses purposive random sampling with 312 samples which represents the Muslim consumer especially students at State Islamic University of Jakarta and Trisakti University. This research applies Structural Equation Model to analyze the model and Mann-Whitney Test to analyze the differences. The finding showed that consumers’ religious behavior significantly influence their intention to purchase halal-labeled products, and only in terms of their intention to purchase halal-labeled products, consumers with Islamic educational background is higher than consumers with general educational background. Because of consumers’ religious behavior is high, consumer intention to purchase halal-labeled products also become elevated.Thus, it is suggested that government and related institutions need to implement the Security Act of Halal Products immediately in order to protect the consumer from consuming non-halal products which are often circulating in Indonesian market and potentially causing social, political and economical turmoil.